Single men's dormitory. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows single men's dormitory at Portland Assembly Center with male evacuees conversing, reading, resting or playing board games. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.